Guidelines of therapeutic design qualities in private hospitals and their hotel accommodation supporting medical tourism in Malaysia - Faraj, Mohamad (2023)
Medical tourists face various challenges during long-term visits, which necessitates better planning when they need to stay longer in the host country. Despite recent interest in healing environments in the Malaysian setting, there has been a scarcity of research attempts investigating its role and impact on medical tourism. Thus, the aim of this study was to explore the therapeutic qualities of medical tourism accommodation facilities that promote patient health in Malaysia. To address the research aim, a qualitative methodology was followed, whereby two data collection techniques were employed: observations of medical tourism hotel accommodations and interviews with relevant stakeholders. Four case study locations were selected for the purpose of data collection in this study. These locations were four hotel accommodations that have formed partnerships with local private healthcare institutions and are popularly utilized by health seeking tourists. An observation checklist for medical tourism hotel accommodations in Malaysia was developed based on a review of the available literature, consisting of elements such as key location, planning, general interior layout, and exterior configuration and features. In addition, elements of the therapeutic environment were defined based on three theories, namely biophilia theory, therapeutic environment characteristics, and environmental stress theory. These elements guided the development of the interview items, which included natural light and view, artificial light, air quality, color, noise, art works, and landscape. The results revealed that the main physical design characteristics that should be provided in therapeutic environments are comfortable furniture and finishings, larger windows for natural lighting and views, improved indoor air quality, more natural elements, better social spaces, and friendly/accessible facilities. Overall, observations of the medical tourism hotel buildings and interviews with stakeholders and patients validated the present research model.